Experimental Study and Numerical Analysis of Floating Crane Catamaran Mooring Tension in Intact and Damage Conditions Using Time-Domain Approach - Eko Budi Djatmiko; Murdjito Murdjito; Mochamad Hanif Rafi’i; Erdina Arianti (International Journal of Offshore and Coastal Engineering, 2021)
Floating Crane Catamaran equipped with a mooring system to keep stable while operating. During operation, wave load causes tension on the mooring system. In this study, the tension of the mooring system was analyzed using experimental studies and numerical analysis with intact and damaged mooring conditions. Experimental studies were carried out by simulating a physical model in the Ocean Basin Maneuvering Laboratory, BTH-BPPT. While numerical using related software. Mooring tension analysis is carried out using the frequency domain approach which refers to the API RP 2SK rules. The sum of the average tension, significant low frequency tension and maximum wave frequency tension is the maximum tension of the mooring system. The low frequency tension and wave frequency tension is obtained by the low-band-pass filter process. The stochastic value is obtained by the FFT of low frequency and wave frequency tension. The results of maximum tension from experimental and numerical at intact conditions, wave headings 90°, Hs 2.5 m, are 373.7 kN and 441.6 kN and at Hs 6.37 m are 565.6 kN and 1741.5 kN. In the damaged condition, wave heading 90°, Hs 2.5 m, the maximum tension is 863.9 kN and 2113.3 kN.